Fracture toughness of steels with nickel content in respect of carbide morphology. (22nd April 2015) - Krawczyk, J.; Pacyna, J.; Bała, P.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper is focused on the influence of Ni addition on the microstructure and fracture toughness of structural steels after tempering. Nickel is known to increase the resistance to cleavage fracture of steel and decrease a ductile–brittle transition temperature. The medium carbon, low alloy martensitic steels attain the best combination of properties in low tempered condition, with tempered martensite, retained austenite and transition carbides in the microstructure. In the present research, four model alloys of different Ni contents (from 0·35 to 4·00%) were used. All samples were in as quenched and tempered condition. Quenching was performed in oil at room temperature. After quenching, samples were tempered at 200°C for 2 h. An increase in nickel content in the investigated model structural steels causes a decrease in ε carbide volume fraction in their microstructure. Cementite nucleates independently in the boundaries of martensite laths and in the twin boundaries in the areas where the ε carbide has been dissolved. It was stated that stress intensity factor KIc significantly decreases in the case of the presence of dispersive elongated cementite precipitations at the boundaries of the prior austenite grains.